2013
DOI: 10.2174/1874120720130701003
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Mathematical Model to Simulate the Single-Breath Nitrogen Washout

Abstract: A nonlinear dynamic model is proposed to reproduce and interpret the influence of pulmonary inhomogeneities on the single-breath nitrogen washout (SBNW) curve. The model is characterized by two parallel zones. In each zone, the upper airways are described by a Rohrer resistor. Intermediate airways are represented as a collapsible segment, the volume of which depends on transmural pressure. Smaller airways are described by a resistance which increases when transpulmonary pressure decreases. The respiratory regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In patients with more severe disease, such a significant increase in the phase III slope may make it difficult to identify the beginning of phase IV. 15 The data of the present study showed an inversely proportional relationship between smoking and CV values in patients with the SERPINA1 gene mutation. We hypothesized that patients with alpha-1 antitrypsin deficiency with a progressively higher smoking load would have progressively more severe COPD.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In patients with more severe disease, such a significant increase in the phase III slope may make it difficult to identify the beginning of phase IV. 15 The data of the present study showed an inversely proportional relationship between smoking and CV values in patients with the SERPINA1 gene mutation. We hypothesized that patients with alpha-1 antitrypsin deficiency with a progressively higher smoking load would have progressively more severe COPD.…”
Section: Discussionsupporting
confidence: 60%
“…In patients with more severe disease, such a significant increase in the phase III slope may make it difficult to identify the beginning of phase IV. 15 …”
Section: Discussionmentioning
confidence: 99%